Pengaruh Variasi Waktu Ekstraksi terhadap Rendemen dan Total Kurkuminoid Ekstrak Etanol 96% Temu Giring (Curcuma heyneana) menggunakan Metode Microwave-Assisted Extraction - Mutia Nur Oktavia; Hanif Rifqi Prasetyawan (Unesa Journal of Chemistry, 2025)
This study aimed to evaluate the effect of extraction time variations on the yield and total curcuminoids of 96% ethanol extract of temu giring (Curcuma heyneana) using the Microwave-Assisted Extraction (MAE) method. Extraction was performed at 20, 60, 120, and 150 seconds using an 800-watt microwave with a 1:10 (w/v) solvent ratio. Yield was calculated based on total solids, while total curcuminoids were quantified using UV-Vis spectrophotometry at 469 nm. The results showed an increase in yield from 2.40% (20 s) to 7.52% (150 s) and total curcuminoids from 2.3962 µg/mL to 5.9593 µg/mL. Statistical analysis indicated a significant difference between treatments (****p < 0, 0001). Based on the tested time range 150-second exteaction time was identified as optimum, maximizing cell rupture and solvent diffusion without compromising thermal stability of curcuminoids. Thus, extraction time plays a key role in optimizing green extraction of temu giring.